2018
DOI: 10.9738/intsurg-d-14-00297.1
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Small Bowel Obstruction Due to Intra-Abdominal Drain: Case Report and Literature Review

Abstract: This is a unique case of a closed-loop bowel obstruction secondary to intra-abdominal drain insertion to illustrate a new complication of drain usage. A 47-year-old patient presents with bowel distention and obstruction. Laparotomy revealed obstructed small bowel looped around a fibrotic tract tracing back to a drain insertion point. This is a case report where a patient suffers rare long-term complications from routine drain insertion. Although beneficial in treating infection and abscess formation after anas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Indeed, surgical drains aid in the earlier detection for better management of complications, and leakage of surgical anastomoses [ 1 , 5 ]. However, it should be noted that several complications of drain usage may lead to significant morbidity and mortality (17%) [ 1 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, surgical drains aid in the earlier detection for better management of complications, and leakage of surgical anastomoses [ 1 , 5 ]. However, it should be noted that several complications of drain usage may lead to significant morbidity and mortality (17%) [ 1 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature has frequently reported the risk of surgical site infections caused by drains, in addition to other complications that have been described such as small bowel evisceration, bronchoperitoneal fistula, and bowel perforation from pressure necrosis [ 4 , 5 , 10 ]. Acute bowel obstruction due to drains remains very uncommon and should be considered, and distinguished from postoperative ileus, in patients with surgical drains presenting post-operative nausea and distention [ 5 , 8 ]. Shah et al described the phenomenon of the obstruction as a “maypole” effect, the vacuum effect of the drain can lead to obstruction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the drainage tube causes intestinal obstruction is still unclear, but this complication was mentioned before. [4,16] In addition, routine drainage can cause other problems such as pain, discomfort and limitation of returning to normal activities of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane study of six randomised controlled trials comparing patients with prophylactic drains and patients without revealed no significant variance in mortality, anastomotic dehiscence, wound infection or other complications. 12 EPSBO is a rare complication that can arise from surgical drain placement, amongst other causes. It is essential to recognise this rare but important cause of EPSBO to prevent more sinister consequences.…”
Section: Early Post-operative Small Bowel Obstruction From Surgical D...mentioning
confidence: 99%
“…A Cochrane study of six randomised controlled trials comparing patients with prophylactic drains and patients without revealed no significant variance in mortality, anastomotic dehiscence, wound infection or other complications 12 …”
Section: Figmentioning
confidence: 99%